Procedural Pain in Lumbar Punctures and the Impact of Preparation in Pediatric Cancer Patients - Sinha, Sudha; Marczak, Magdalena; Jacob, Jean; Palat, Gayatri; Brun, Eva; Wiebe, Thomas; Schyman, Tommy; Segerlantz, Mikael (Indian Journal of Medical and Paediatric Oncology, 2019)
Aim: Childhood cancer patients are subjected to recurring painful medical procedures. In low- and middle-income countries (LMIC), where the majority of the world’s childhood cancer patients live, pain management is often unsatisfactory due to limited resources. This study aimed to evaluate the possibility of conducting a preprocedural preparation for lumbar punctures (LPs) at a pediatric oncology unit in a LMIC and to assess whether this intervention would decrease procedural pain and fear. Methods: Patients aged 5–18 who underwent LPs between February 25, 2017, and April 12, 2017, were eligible and invited to participate. Included patients were interviewed to assess the procedural pain and fear in conjunction with the LP and the patients’ understanding of why an LP was done. Closest caregivers and the medical staff were interviewed to compare the perceptions of pain. The study was conducted in two separate phases; patients included in the period of February 25–March 9 underwent LP according to routines without preparation while patients included in the period of March 10–April 12 received procedural preparation with information. Results from the interviews from the two study groups were compared. Results: Out of 79 patients who met the inclusion criteria, 76 were included and preparation was successfully implemented for 25 of them. The pain decreased significantly (P = 0.022) after preparation. The physicians underestimated the patients’ pain (P < 0.0001). The understanding of the reason for the LP increased significantly among patients (P = 0.0081) and their caregivers (P < 0.0001). Conclusions: Preparation by preprocedural information, created to fit the situation at a state-run hospital in a LMIC, is feasible and efficient.
Keywords: Low/middle-income countries; pediatric oncology; preprocedural preparation; procedural pain